2011
DOI: 10.1007/s10710-011-9131-8
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of standard cell libraries for future technology nodes

Abstract: Evolvable Hardware has been a discipline for over 15 years. Its application has ranged from simple circuit design to antenna design. However, research in the field has often been criticised for not addressing real world problems. Intrinsic variability has been recognised as one of the major challenges facing the semiconductor industry. This paper describes an approach that optimises designs within a standard cell library by altering the transistor dimensions. The proposed approach uses a Multi-objective Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This seminal work has been extended in several ways. The most recent research in the area of digital circuits includes the evolution of novel standard cell libraries for future tech nology nodes [3] and a post synthesis optimization of complex combinational circuits using formal verification principles [4]. While the achievable quality of resulting design/optimization is usually very high, the computational time required to achieve that result is the main drawback.…”
Section: Introductionmentioning
confidence: 99%
“…This seminal work has been extended in several ways. The most recent research in the area of digital circuits includes the evolution of novel standard cell libraries for future tech nology nodes [3] and a post synthesis optimization of complex combinational circuits using formal verification principles [4]. While the achievable quality of resulting design/optimization is usually very high, the computational time required to achieve that result is the main drawback.…”
Section: Introductionmentioning
confidence: 99%
“…Most severely affected designs are SRAMs and latches, which are fundamental elements of any current programmable logic architecture. The results in [5], [16], [17], which have been obtained from statistical SPICE simulations, suggest that optimising the widths of transistors in standard cells can improve their variability tolerance, speed and power consumption. It has been also shown that it is possible to design and optimise analogue CMOS circuits in hardware using field programmable transistor arrays (FPTAs) [14], [18].…”
Section: Inspiration From Fpta Architectures and Variation-aware mentioning
confidence: 98%
“…It has been also shown that it is possible to design and optimise analogue CMOS circuits in hardware using field programmable transistor arrays (FPTAs) [14], [18]. Therefore, if FPTA based mechanisms to alter device sizes according to [5] could be incorporated in hardware, it would be possible to optimise designs post fabrication in a dynamic fashion. This would not only have the advantage of being able to enhance variability tolerance and performance for a specific design, but could also account for variations between different devices.…”
Section: Inspiration From Fpta Architectures and Variation-aware mentioning
confidence: 99%
See 1 more Smart Citation
“…The circuit topology and functionality optimisation can be considered as a combinatorial optimisation problem. The ability of evolutionary algorithms to handle combinatorial optimisation problems using genetic algorithm makes them an interesting candidate to solve this problem [8]- [11]. This paper, for the first time, develops a comprehensive methodology to extract device and circuit parameters (including variability information) from motif structures, and uses these parameters in an EA driven circuit simulator to optimise standard cells through an evolutionary algorithm.…”
Section: Introductionmentioning
confidence: 99%